Trends and outcomes of acute pulmonary embolism transfers: a nationwide cohort sample 2008–2018. (14th October 2021) - Elkaryoni, A; Allen, S; Newman, J; Fareed, J; Bechara, C; Bunte, M; Darki, A
Abstract: Background: Acute pulmonary embolism (PE) is associated with a high morbidity and mortality. There is paucity of data describing outcomes of patients with PE transferred from a different acute care hospital. We hypothesized that outcomes of patients transferred for PE care may be suboptimal potentially as a result of treatment delays due to non-protocolized transfer plan for this cohort of patients. Methods: We used the Nationwide Inpatient Sample (NIS) from 2008–2018 to identify patients hospitalized with a primary diagnosis of acute PE by using International Classification of Diseases-9th, and 10th revision-clinical modification codes. Patients were subgrouped according to the transfer status by using the NIS transfer data element. The primary outcome was in-hospital mortality. The secondary outcomes were the annual trends of PE transfers and in-hospital mortality over study period. Chi-square test was used to compare categorical variables while Mann-Whitney U test was used for continuous variables. A multivariate logistic regression model of clinically relevant variables including hypertension, diabetes mellitus, atrial fibrillation, heart failure, coronary artery disease, chronic lung disease, chronic kidney disease, length of stay, age, and gender were conducted for the primary outcome. Results: A total of 396, 214 patients with an acute PE met inclusion criteria. Among this patient cohort, 8.1% of patients were transferred from an outside facility. Patients that were transferred for PE management were older [median age 66.0 years (interquartile range (IQR), 49–83) vs 64.0 (IQR, 48–80) years, p<0.001], had longer length of stay [median 5.0 (IQR, 1–9) days vs 4.0 (IQR, 1–7) days, p<0.001], and had a higher number of comorbidities. The in-hospital mortality among PE transfers was higher compared to those that were not transferred (5.7% vs 2.8%, p<0.001). After adjustment using multivariate regression model, transfer for PE care was associated with increased risk of mortality (odds ratio 1.8 (95% confidence interval, 1.1–2.9; p=0.013). Transfers for PE care notably increased over the study period (5.8% in 2008 to 11.3% in 2018, p<0.001). Trends of in-hospital mortality among PE transfers did not change over time while there was a decrease in mortality among patients that were not transferred for management of their PE (3.2% in 2008 to 2.6% in 2018, p<0.001). Conclusion: Patients transferred for PE care tend to be more complex and have a higher risk of mortality relative to patients that do not require transfer of care. Despite the increased transfer rate of PE patients over time, the mortality rates have not improved. Further prospective research should evaluate the characteristics of treatment and further assess patient risk to help develop transfer protocols that may reduce risk for patients with PE requiring higher acuity care. Funding Acknowledgement: Type of funding sources: None.